Where authority, speech acts and modality meet: A pragmatic analysis of the trial record of King Charles I - Minako Nakayasu; Michi Shiina (LingBaW)
This paper investigates how speakers perform speech acts coordinating with modality in the flux of power in Early Modern courtroom interactions along the lines of historical pragmatics. The text used for analysis is the trial record of King Charles I in the Sociopragmatic corpus, in which the King was put on trial on the charge of high treason.